Multiple acute infarcts in the posterior circulation. Issue 3 (March 1996) - Bernasconi, A; Bogousslavsky, J; Bassetti, C; Regli, F
Abstract : OBJECTIVE–to evaluate clinical, radiological, and prognostic features of patients with multiple acute infarcts in remote arterial territories of the posterior circulation. DESIGN–Data analysis from a prospective acute stroke registry in a community based primary care centre using a standard protocol including MRI and MRA. RESULTS–In three and a half years, 27 of the 236 patients (11%) with posterior circulation stroke had multiple acute infarcts in the posterior circulation as shown by gadolinium enhancement on MRI. Eighteen patients had multiple infratentorial and supratentorial infarcts including the cerebellum and posterior cerebral artery territory, with coexisting brainstem involvement in seven patients. Fourteen patients had a rostral basilar artery syndrome and cerebellar signs; four patients had a visual field defect with cerebellar signs. Causes were vertebral (six) or basilar (four) artery atheromatosis, and cardioembolism (four). Seven patients had multiple acute infarcts in the posterior circulation of the cerebellum and lower brainstem. Brainstem and cerebellar signs were found in most patients (five); aetiologies were small vessel disease (four), cardioembolism (one), and vertebral artery dissection (one). Two patients with large artery atheromatosis had multiple acute infarcts in the posterior circulation in the brainstem and posterior cerebral artery territory. One month after stroke more than 25% of the patients were dependent or had died. There was no difference in the outcome between the three groups, and recovery was linked to the size of infarcts rather than to a high number of infarcts. CONCLUSIONS–multiple acute infarcts in the posterior circulation usually involve the cerebellum. Simultaneous brainstem and posterior cerebral artery territory infarcts sparing the cerebellum are uncommon. They can be suspected clinically before neuroimaging, mainly when supratentorial and infratentorial infarcts coexist. This may be important, because different patterns of infarction are associated with different causes of stroke.